'Chest epilepsy' in a child. Issue 799 (May 1992) - Gulati, S.; Kumar, L.
Abstract : Pain is a most unusual manifestation of epilepsy, and it is rarer still for chest pain to be the primary manifestation of a seizure disorder. We report here a 6 year old boy with epileptic chest pain--'chest epilepsy'--an entity not previously described in children.